Integration of Multicultural Values in Elementary Social Studies Learning: Conceptual Analysis Based on Character Education Literature - Hermansyah; Sundari; Tinuk Triyana; Sabar Narimo; Muhammad Musiyam (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aims to conceptually analyze the integration of multicultural values based on character education in Social Sciences (IPS) learning in elementary schools. The focus of the study is directed at the mapping of essential multicultural values, their integration strategies in social studies learning, and their impact on the formation of students' character in the context of a multicultural Indonesian society. This research uses the library research method by examining various library sources in the form of academic textbooks, reputable national and international journal articles, curriculum documents, and relevant previous research results. The data analysis technique is carried out through systematic content analysis with the stages of identification, theme classification, interpretation, and conceptual synthesis of selected literature. The results show that multicultural values such as tolerance, empathy, equality, social justice, and respect for diversity have been substantially contained in the goals and scope of social studies learning, but are still implicit and have not been optimally integrated in learning practices. The integration of multicultural values based on character education through social studies has been proven to have the potential to strengthen the formation of students' social character, especially in the development of tolerant, democratic, and inclusive attitudes. Therefore, it is necessary to strengthen a holistic, participatory, and contextual social studies learning design so that social studies learning is not only oriented to cognitive aspects, but also to internalizing values and forming students' multicultural character